2020
DOI: 10.1590/1984-0462/2020/38/2018065
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic Uremic Syndrome Associated With Streptococcus Pneumoniae in Pediatrics: A Case Series

Abstract: Objective: To describe a case series of four (4) patients with hemolytic uremic syndrome due to Streptococcus pneumoniae in a level four complexity institution in the city of Bogotá, D.C., Colombia. Cases description: We describe cases of four patients who presented respiratory symptoms and fever. All four patients were in regular conditions on hospital admission, after which they required intensive care and ventilatory support. Upon admission, three cases showed evidence of pleuropulmonary complication. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…1,5 El mecanismo fisiopatológico de esta entidad aún no está bien definido. Se cree que la neuraminidasa producida por el Streptococcus pneumoniae elimina el ácido N-acetilneuramínico de diversas glicoproteínas y glicolípidos de la superficie de membrana de eritrocitos, plaquetas y capilares glomerulares, exponiendo de este modo el antígeno de Thomsen-Friedenreich (antígeno T), 2,3,6 Tabla 1: Comparación de reportes de casos con síndrome hemolítico urémico por Streptococcus pneumoniae.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…1,5 El mecanismo fisiopatológico de esta entidad aún no está bien definido. Se cree que la neuraminidasa producida por el Streptococcus pneumoniae elimina el ácido N-acetilneuramínico de diversas glicoproteínas y glicolípidos de la superficie de membrana de eritrocitos, plaquetas y capilares glomerulares, exponiendo de este modo el antígeno de Thomsen-Friedenreich (antígeno T), 2,3,6 Tabla 1: Comparación de reportes de casos con síndrome hemolítico urémico por Streptococcus pneumoniae.…”
Section: Discussionunclassified
“…el cual reacciona con el anticuerpo anti-T, presente en la mayoría de los individuos, dando lugar a la tríada clásica característica del SHU. 2,6 La neumonía complicada constituye la presentación inicial más frecuente asociada al SHU-SP (hasta en 90% de los casos), 2,4 seguida de meningitis. El SHU-SP en comparación al SHU desencadenado por Escherichia coli tiene peor pronóstico.…”
Section: Wwwmedigraphicorgmxunclassified
See 2 more Smart Citations
“…In their recent article, Hemolytic-uremic syndrome associated with Streptococcus pneumoniae in pediatrics: a case series, published in Revista Paulista de Pediatria, Guerra et al 1 reported four cases of thrombotic microangiopathy (TMA) related to pneumococcal infection in the unicentric pediatric population of Bogotá, Colombia. One can highlight the excellence in the management of these cases, which is exemplified by the absence of deaths and recovery of renal function in three of the four children.…”
mentioning
confidence: 99%